Serious game for teaching a computing subject - Ankit Wal (2015)
This project, as the name suggests, is a comprehensive study of the entire process of design and development of a serious game for the purpose of teaching a computing subject. This project primarily investigates whether optimising game play can achieve sufficient engagement to aid learning . The research into serious games is a relatively new field of study. The application of computer or video games to a teaching context is widely considered to be an aid to the learning process. However, the extent of this benefit is still contested and empirical data on the subject is not particularly common place. The evaluation of the effectiveness of the serious games does not yet have universally accepted standard metrics. The use of computer and video games in classrooms is an obvious extension of the ‘gamification’ of educational material. The introduction of game elements into learning material is the most common design methodology to produce serious games. The purpose of this project was to define and differentiate between approaches to serious game design. We examine the effectiveness of a fairly new approach of “Game first, learning second” and identify the key game mechanics that contribute to the learning. A 3D adventure/discovery game was developed with the unity3D game engine, with the learning objective being ‘rules governing drawing a UML2 communication diagram’. The report identifies key findings from similar projects and tests them against results obtained by a post game based learning session survey. The game was developed and designed specifically for the purpose of this project and tested on a sample size of 75 students. The ‘Game First’ approach proved to be a successful model of serious game design and the game created sufficient incentivisation by game play mechanics to aid in the study of the learning material. The standard metrics of the psychological need satisfaction also proved to be an effective indicator of the success of a ‘Game First’ serious game.